Knowledge regarding diabetes among expectant mothers attending ante natal clinic of a tertiary care institution of Kolkata: a cross sectional study - Biswas, Prabir; Majumdar Das, Sonali; Das, Bibekananda (International Journal of Research in Medical Sciences, 2018)
Background: Prevalence of gestational diabetes (GDM) has increased tremendously in India. Prevention of the condition is possible through health education. However, knowledge regarding diabetes is poor among Indian women. Thus, examining the basic knowledge regarding diabetes among expectant mothers is necessary to identify areas of deficit. Methods: An observational, analytical study of cross-sectional design was undertaken to assess the knowledge regarding diabetes among 173 expectant mothers attending the ante-natal clinic of R. G. Kar Medical College, Kolkata using a pre tested schedule. Results: Mean score of the respondents were less than 3 out of 8 which was a poor score. The overall mean diabetic score was similar for the antenatal mothers irrespective of the number of pregnancy (p=0.3154) but the score was greater than that for the non-pregnant women (p=0.0000). The expectant mothers showed better response compared to the controls when asked whether a person can have diabetes but be unaware of the condition; whether diabetes can harm a person’s body before diagnosis; long term complications of the disease(P<0.05). However, answers were similar across all groups with respect to queries like the age group in which the condition is more commonly diagnosed and whether diabetes is curable (p>0.05). The pregnant women had less reported leisure time physical exercise and first degree relative with diabetes (p<0.05). Conclusions: Mean knowledge score of the expectant mothers was more than the women controls though the overall score was poor. A structured awareness program is urgently needed which would first address diabetes in general and then the specifics of GDM.